Ultrastructure of Besnoitia cysts from reindeer (Rangifer tarandus tarandus L) - Hilali, Mosaad; Rehbinder, Claes; Nikkilä, Tapio (Rangifer, 1990)
The ultrastructure pf Besnoitia cysts in reindeer is described. The observations made on Besnoitia cysts and merozoites indicate a form distinct enough to be placed in a new species - Besnoitia tarandi.